A prospective economic analysis of OSHA's heat injury and illness prevention rules - Joseph S. Tracy; Matthew E. Kahn (American Enterprise Institute (AEI), 2025)
During the Biden Administration, the Occupational Safety and Health Administration (OSHA) proposed new rules to protect workers from heat exposure. The intent of this regulation was to improve worker quality of life and reduce health impacts. In this paper, we explore the trends in heat-related worker injuries and the likely unintended consequences of this proposed regulation. By pointing out these "Peltzman Effects", we seek to highlight the existing data gaps that limit the regulator's efforts to improve worker quality of life and the opportunities for market-based mitigation of these heat-related risks.
Keywords: 330